Complex medical history of a patient with a compound heterozygous mutation in C1QC. (September 2019) - Lubbers, R; Beaart-van de Voorde, L J J; van Leeuwen, K; de Boer, M; Gelderman, K A; van den Berg, M J; Ketel, A G; Simon, A; de Ree, J; Huizinga, T W J; Steup-Beekman, G M; Trouw, L A
Introduction: C1q is an essential part of the classical pathway of complement activation. Genetic deficiencies, caused by homozygous mutations in one of the C1q genes, are rare and are strongly associated with development of systemic lupus erythematosus (SLE). Here we describe a C1q-deficient patient with a compound heterozygous mutation. Material and methods: Serum was analysed with enzyme-linked immunosorbent assay (ELISA) and Western blot for the presence of C1q, and DNA and RNA sequencing was performed to identify the mutations and confirm that these were located on different chromosomes. Results: The medical history of the patient includes SLE diagnosis at age 11 years with cerebral involvement at age 13, various infections, osteonecrosis and hemophagocytic syndrome. Using ELISA and Western blot, we confirmed the absence of C1q in the serum of the patient. Using DNA sequencing, two mutations in the C1QC gene were identified: c.100G > A p.(Gly34Arg) and c.205C > T p.(Arg69X). With RNA sequencing we confirmed that the mutations are located on different chromosomes. Discussion: The patient described in this case report has a compound heterozygous mutation in C1QC resulting in C1q deficiency.